1991
DOI: 10.1128/jb.173.2.549-558.1991
|View full text |Cite
|
Sign up to set email alerts
|

Dual regulation of the ugp operon by phosphate and carbon starvation at two interspaced promoters

Abstract: The ugp operon of Escherichia coli includes genes involved in the uptake of sn-glycerol-3-phosphate and glycerophosphoryl diesters and belongs to the pho regulon which is induced by phosphate limitation. This operon has two transcriptional initiation sites, as determined by SI nuclease mapping of the in vivo transcripts. The downstream promoter has multiple copies of the pho box, the consensus sequence shared by the pho promoters; the upstream promoter has a consensus sequence for the promoters regulated by cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
62
0
1

Year Published

1992
1992
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(67 citation statements)
references
References 28 publications
4
62
0
1
Order By: Relevance
“…They contain at least one unit of the pho box, and some pho genes such as pstS and ugpB have two and three pho boxes tandemly re1Corresponding author. peated, respectively (Kimura et al 1989;Kasahara et al 1991). Deletion analysis of these promoter regions also indicated that the pho box proximal to the -10 region is required for the expression of these genes.…”
mentioning
confidence: 99%
“…They contain at least one unit of the pho box, and some pho genes such as pstS and ugpB have two and three pho boxes tandemly re1Corresponding author. peated, respectively (Kimura et al 1989;Kasahara et al 1991). Deletion analysis of these promoter regions also indicated that the pho box proximal to the -10 region is required for the expression of these genes.…”
mentioning
confidence: 99%
“…The comparison of the PhoB E -DNA arrangement in the complex with a 23-bp DNA-mer (Blanco et al , 2002 ), which forms pseudo-continuous protein-DNA fibers, with the one in complex with a 26-bp DNA-mer (this work) reveals that the higher DNA bending in the former promotes contacts between adjacent PhoB E dimers. A previous in vivo study on transcription using pho box deletions of the ugpB promoter fused to a reporter gene also gave clues about hierarchical and cooperative binding (Kasahara et al , 1991 ). Although the authors did not relate their findings to cooperative binding, their results showed that at cellular concentrations of PhoB the intermediate pho box was required for the protein to bind to the downstream box and activate transcription.…”
mentioning
confidence: 61%
“…Transcriptional activation from E. coli pho-regulated promoters has been shown to be dependent on the product of the phoB gene, PhoB (16,20). To determine whether the pho-activated promoters identified within the Acinetobacter PHA biosynthetic gene locus behaved similarly to these promoters, primer extensions were performed on RNA isolated from E. coli wild-type and phoB mutant strains containing pJKD1425.…”
Section: Vol 177 1995 Transcriptional Regulation Of Pha Genes By Phmentioning
confidence: 99%